(Pd–CuCl2)/γ-Al2O3: a high-performance catalyst for carbonylation of methyl nitrite to dimethyl carbonate1. Issue 6 (27th June 2015) - Lv, Dong-Mei; Xu, Zhong-Ning; Peng, Si-Yan; Wang, Zhi-Qiao; Chen, Qing-Song; Chen, Yumin; Guo, Guo-Cong
<x xml:space="preserve">Abstract</x> (Pd–CuCl2)/γ-Al2O3 catalyst with excellent activity and selectivity was successfully developed for vapor-phase carbonylation of methyl nitrite to dimethyl carbonate (DMC).